De Haas-van Alphen oscillation in both the normal and superconducting mixed states of NbSe2, CeRu2, URu2Si2, and UPd2Al3 (Review Article): - Inada, Y.; Onuki, Y. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 1999)
The de Haas-van Alphen (dHvA) oscillation was observed clearly in both the normal and superconducting mixed states in NbSe2,CeRu2, URu2Si2, and UPd2Al3. The dHvA frequency, which is proportional to the extremal cross-sectional area of the Fermi surface, does not change in magnitude between the normal and mixed states. For the f-electron superconductors, the cyclotron effective mass is found to be reduced and the corresponding Dingle temperature or scattering rate of the conduction electron increases in the mixed state. An anisotropic energy gap with a line node for URu2Si2 and UPd2Al3 is discussed from the angular dependence of the dHvA amplitude in the mixed state.